ظاهرة إختطاف الأطفال وإنعكاساتها على عوامل التحصيل الدراسي - بوعنان، سمية, بن نونة، كريمة (جامعة الوادي university of Eloued, 2017)
Study summary in English: The aim of this study was to uncover the phenomenon of kidnapping and its relation to the factors of educational achievement in the students, as well as to the extent of fear of this phenomenon and its impact on student achievement. The nature of the study required the descriptive approach, which is one of the most widely used methods in the social sciences. In this study, the sample was selected in a fundamental way. It was selected from two elementary schools in the Wilaya of Al-OUED to select 81 students divided into 41 primary students. The tools used to collect the data included the questionnaire designed by the research members, which included 30 items divided into three axes according to the hypotheses The statistical methods adopted in the study are percentage and frequency. We have reached the following conclusions: There is no relationship between the reflection of child abduction phenomenon and the motivation to learn. There is no relationship between the reflection of child abduction phenomenon and attention within the department. There is a relationship between the reflection of child abduction and classroom interaction.
دراسة ميدانية على تلاميذ سنة الخامسة إبتدائي بإبتدائيتي بوعنان بالقاسم وانصيرة المولدي
مذكرة ماستر علوم اجتماعية تخصص علم اجتماع التربية
Keywords: ظاهرة الإختطاف، التحصيل الدراسي; Le phénomène des enlèvements, de la réussite scolaire; The phenomenon of abduction, academic achievement